Soil and the foliage nutrient status following soil amendment applications in a Japanese cypress (Chamaecyparis obtusa Endlicher) plantation. (3rd April 2017) - Jeong, Jaeyeob; Jo, Chang Gyu; Baek, Gyeong Won; Park, Jae-Hyun; Ma, Ho-Seop; Yoo, Byung Oh; Kim, Choonsig
ABSTRACT: The aim of this study was to evaluate the response of soil amendment applications on soil and the foliage nutrient status of a Japanese cypress ( Chamaecyparis obtusa Endlicher ) plantation established following clear-cutting in a pine-wilt-disease (PWD)-disturbed forest. We established four soil amendment treatments [(compound fertilizer (CF), compound fertilizer + biochar (CFB), compound fertilizer + sawdust (CFS) and a non-treated control treatment] in an 8-year-old Japanese cypress plantation. Soil organic carbon (C) and total nitrogen (N) were not significantly different ( P  > 0.05) between the soil amendment treatments and the control treatments, whereas extractable phosphorus (P), NH4 +, K +, and Mg 2+ concentrations were significantly affected by the addition of biochar in CF. The mean soil CO2 efflux rates during the study period were the highest in CFB (0.79 g CO2  m −2 h −1 ), followed by CFS (0.71 g CO2  m −2 h −1 ), CF (0.62 g CO2  m −2 h −1 ), and the control (0.46 g CO2  m −2 h −1 ) treatments. Foliar N and P concentrations were significantly higher in the CFB than in the control treatments. The results suggest that the addition of biochar in CF can enhance extractable soil nutrients and foliar N and P conditions of Japanese cypress established in a PWD-disturbed forest.